Clermont-Ferrand versus Vectec uterine manipulator for total laparoscopic hysterectomy. Issue 1 (2nd January 2019) - Misirlioglu, Selim; Boza, Aysen; Urman, Bulent; Taskiran, Cagatay
Abstract: Objective: To compare the operation time and performance of two uterine manipulators used for total laparoscopic hysterectomy (TLH). Material and methods: Design: Retrospective cohort analysis. Design classification: Canadian Task Force Classification II-2. Setting: Tertiary-care university-based teaching hospital and academic affiliated private hospital. Patients: All consecutive patients who underwent for TLH between January 2014 and June 2017. All operations were performed by two expert endoscopic surgeons using one of the following uterine manipulators depending on surgeon preferences: Clermont-Ferrand (CF) or Vectec (VT) MAUT60. Patients were excluded if additional surgeries such as urogynecological procedures were performed, TLH was converted to laparotomy prior to colpotomy, and when their operation records could not be obtained. A total of 169 patients were added to final analysis. Operation time, colpotomy time and the subjective performance of manipulators such as movement of the uterus, visualization of the vaginal fornices, and maintenance of pneumoperitoneum were evaluated by watching un-edited operation videos. Results: A total of 169 patients (83 patients in CF group; 86 patients in VT group) were included in the final analysis. Patients' baseline characteristics were comparable between groups. Operation time and time required for colpotomy were significantly shorter in the VT group. Lateral movements of the manipulators and elevation of the uterus were better with VT compared to CF ( p  = .001 for both). Compared to the CF, VT was superior for visualization of the vaginal fornices ( p  = .004) and maintenance of pneumoperitoneum ( p  < .001). Both surgeons had perfect agreement on the performance grading of manipulators ( p  < .001, Kappa values were between 0.86–0.92). There was no difference between groups in estimated blood loss and duration of hospital stay. Reinsertion or the need to change the manipulator was not required in either group. No pelvic or vaginal abscess, cuff cellulitis, dehiscence, or hematoma formations were noted. Conclusion: Laparoscopic hysterectomy assisted with the VT uterine manipulator is associated with shorter operation and colpotomy time. Furthermore, the movements of uterus, visualization of the vaginal fornices, and maintenance of pneumoperitoneum were significantly better with VT compared to the CF manipulator.